Pediatric Blunt Neck Trauma Causing Esophageal and Complete Tracheal Transection. (4th March 2017) - Nicholson, Benjamin; Dhindsa, Harinder; Seay, Louis
ABSTRACT: Background: Blunt injuries to the cervical trachea remain rare but present unique and challenging clinical scenarios for prehospital providers. These injuries depend on prehospital providers either definitively securing the injured airway or bridging the patient to a treatment facility that can mobilize the necessary resources. Case Summary: The case presented here involves a clothesline injury to a pediatric patient that resulted in complete tracheal transection and partial esophageal transection. Ground and air prehospital providers utilized a stepwise approach to this airway injury and achieved a favorable outcome. The patient was serendipitously intubated through a blind nasal approach that entered the proximal esophagus, exited through the tear and entered the distal trachea. Discussion: There is a paucity of literature describing the successful management of these devastating injuries. While some authors have advocated for early flexible fiberoptic intubation or proceeding directly to tracheostomy, these techniques are not available in the prehospital environment. This case also highlights the inherent issues with proceeding to cricothyroidotomy in patients with tracheal trauma and should give all providers pause before considering this management technique. Conclusion: Ultimately, a systematic approach to all airways will ensure that prehospital providers are best prepared for even the most challenging scenarios.